The APC10 subunit of the anaphase‐promoting complex/cyclosome orchestrates NLRP3 inflammasome activation during the cell cycle. Issue 19 (30th August 2021) - Huang, Siyu; Wan, Pin; Huang, Shanyu; Liu, Siyu; Xiang, Qi; Yang, Ge; Shereen, Muhammad Adnan; Pan, Pan; Wang, Jun; Liu, Weiyong; Wu, Kailang; Wu, Jianguo
Abstract : The activation of the NLRP3 inflammasome plays a crucial role in the innate immune response. During cell division, NLRP3 inflammasome activation must be strictly controlled. In this study, we discover that the anaphase‐promoting complex subunit 10 (APC10), a substrate recognition protein of the anaphase‐promoting complex/cyclosome (APC/C), is a critical mediator of NLRP3 inflammasome activation. During interphase, APC10 interacts with NLRP3 to promote NLRP3 inflammasome activation, whereas during mitosis, APC10 disassociates from the NLRP3 inflammasome to repress inflammatory responses. This study reveals a distinct mechanism by which APC10 serves as a switch for NLRP3 inflammasome activation during the cell cycle. Abstract :